2000
DOI: 10.1001/jama.283.11.1445
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin and Pyrazinamide vs Isoniazid for Prevention of Tuberculosis in HIV-Infected Persons<SUBTITLE>An International Randomized Trial</SUBTITLE>

Abstract: Our data suggest that for preventing tuberculosis in HIV-infected patients, a daily 2-month regimen of rifampin and pyrazinamide is similar in safety and efficacy to a daily 12-month regimen of isoniazid. This shorter regimen offers practical advantages to both patients and tuberculosis control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
116
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(123 citation statements)
references
References 23 publications
(18 reference statements)
4
116
1
2
Order By: Relevance
“…This rate of rifampin and pyrazinamide toxicity is comparable to rates reported in recent years from several observational studies and two clinical trials in individuals without HIV infection (23)(24)(25)(26)(27)(28)(29), but is substantially higher than rates reported in clinical trials of patients with HIV infection (7)(8)(9).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This rate of rifampin and pyrazinamide toxicity is comparable to rates reported in recent years from several observational studies and two clinical trials in individuals without HIV infection (23)(24)(25)(26)(27)(28)(29), but is substantially higher than rates reported in clinical trials of patients with HIV infection (7)(8)(9).…”
Section: Discussionsupporting
confidence: 79%
“…Several studies of rifampin-based short-course regimens for latent TB have shown similar or superior efficacy to longer courses of INH (6)(7)(8)(9). Rifapentine is a long-acting rifamycin with activity comparable to rifampin but with a prolonged half-life that permits weekly dosing (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Studies have documented that LTBI treatment given to HIV-positive persons will reduce the risk of developing active TB by 62-80%, and preventive LTBI treatment among HIV-infected persons is an important part of the TB control strategy worldwide. [18][19][20][21][22] In recognition of the risk of starting LTBI treatment in a person with active TB, there is a need for clear recommendations about how to rule out active disease ahead of treatment. In our study, sputum samples for culture were collected from 70% of the participants before treatment, of whom 63% were culture-negative at…”
Section: Public Health Action Ltbi In Norway 169mentioning
confidence: 99%
“…In this setting, BCG-immunized mice are better able to restrict the growth of M. tuberculosis infection, leading to smaller bacterial populations that are more representative of LTBI in humans (33)(34)(35). This model proved its utility when it was used to demonstrate the superior activity of short-course RIF plus PZA over that of INH (33), a finding that prompted the clinical development of the former highly efficacious combination regimen (4)(5)(6).…”
mentioning
confidence: 99%